Reconfigurable Disc Trees for Visualizing Large Hierarchical Information Space - Jeong, Chang-Sung; Pang, Alex (InfoVis'98: Proceedings of the IEEE Symposium on Information Visualization, 1998)
We present a new visualization technique, called RDT (Reconfigurable Disc Tree) which can alleviate the disadvantages of cone trees significantly for large hierarchies while maintaining its context of using 3D depth. In RDT, each node is associated with a disc around which its children are placed. Using discs instead of cones as the basic shape in RDT has several advantages: significant reduction of occluded region, sharp increase in number of displayed nodes, and easy projection onto plane without visual overlapping. We show that RDT can greatly enhance user perception by transforming its shapes dynamically in several ways:(1) disc tree which can significantly reduce the occluded region by the foreground objects, (2) compact disc tree which can increase the number of nodes displayed on the screen, and (3) plane disc tree which can be mapped onto the plane without visual overlapping. We describe an implementation of our visualization system called VISIT (Visual Information System for reconfigurable dIsc Tree). It provides 2D and 3D layouts for RDT and various user interface features such as tree reconfiguration, tree transformation, tree shading, viewing transformation, animation, selection and browsing which can enhance the user perception and navigation capabilities. We also evaluate our system using the following three metrics: percentage of occlusion, density of displayed nodes on a screen. number of identifiable nodes.